Evaluation of the insertion program and accessibility of employees with disabilities in the workplace: a case study in a brewery (Research, Society and Development, 2020)
Work is one of the forms of inclusion for people with disabilities, which favors development, potential and capacity, thus providing their recognition before society. This article aims to evaluate the insertion and accessibility program for employees with disabilities in the workplace in a brewing company. The methodology was through a case study, through observational research. During the observation, it was noticed that the company sought to adopt a policy of inclusion of people with disabilities, because it met most of the requirements and adaptations necessary for people with disabilities to be able to move and live with other employees. However, the company under study has not met all normative requirements related to accessibility. Despite the efforts to adapt its physical facilities, there are still some adaptations that are not impossible for the company to fulfill.